TEKNIK PEMBELAJARAN MAHARAH BAHASA ARAB - Nur Rokhhmatulloh (Universitas Yudharta Pasuruan, 2017)
Engineering is an attempt to apply certain teaching methods in the classroom. In other words, technique is a specific activity that is implemented in the classroom in accordance with the method and approach chosen. Thus the approach is axiomatic, methods are procedural and techniques are operational-implementative.The technique which in Arabic is ushlub is the same as strategy (this last term is used in this paper). Strategic is implementational, meaning what actually happens in the classroom to achieve learning objectives. Therefore this active Arabic learning strategy is grouped into four categories, namely listening learning strategies, speaking, writing, and grammar.